Kiprah Kerajaan Islam Dalam Penyebaran Islam di Indonesia - Yahya, Iffatussabrina; Putri, Lutfia Aisyah; Hidayat, M. Zikri; Riadi, Muhammad Akbar; Agung, Muhammad Ariiq Alhafizh; Gusmawarni, Mutia; Domo, Arrasyidin Akmal (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
The role of Islamic kingdoms before the colonial era significantly influenced the spread of Islam in Indonesia. They succeeded in forming and developing an Islamic education system different from the Dutch colonial education system. This research conducted a qualitative analysis of various historical and literary sources to explore the contribution of Islamic kingdoms to the spread of Islam in Indonesia. The results showed that Islamic kingdoms played a crucial role in Dakwah activities and in forming Islamic educational institutions such as pesantren. They also contributed to the development of Islamic culture through arts, literature, architecture, and so on. Therefore, understanding the history of Islamic kingdoms in Indonesia is crucial in comprehending the country's development of religion, culture, and education.